2015
DOI: 10.1080/00220388.2014.997218
|View full text |Cite
|
Sign up to set email alerts
|

Loan Officers’ Gender and Microfinance Repayment Rates

Abstract: This study examines the impact of loan officer characteristics on repayment rates of microfinance borrowers in Mexico applying multilevel analyses, with special attention to the impact of the gender of the loan officer on default rates. The results strongly suggest that loan officers play a crucial role in improving repayment rates in microfinance and that male loan officers are better able to induce borrowers to repay than female loan officers. This may be because men exert authority over women and face fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
7
33
1
Order By: Relevance
“…In other words, they are characteristic of the enabling organizational structures and management systems of commercial, standardized and low-cost models of microfinance implementation with insufficient social-performance monitoring and framework. The external validity of the practice-drift phenomenon is therefore likely to go beyond the specific context of the villages and institution examined here, and have bearing on contexts where similar low-cost models are operating and where analogous institutional practices have been reported (van den Berg et al, 2015;Takahashi et al, 2010). If microfinance is to achieve its social mission there is a need, as illustrated in this article, for new approaches and efforts to understand how commercialization shapes the practice of microfinance in the lives of its clients.…”
Section: Resultsmentioning
confidence: 96%
“…In other words, they are characteristic of the enabling organizational structures and management systems of commercial, standardized and low-cost models of microfinance implementation with insufficient social-performance monitoring and framework. The external validity of the practice-drift phenomenon is therefore likely to go beyond the specific context of the villages and institution examined here, and have bearing on contexts where similar low-cost models are operating and where analogous institutional practices have been reported (van den Berg et al, 2015;Takahashi et al, 2010). If microfinance is to achieve its social mission there is a need, as illustrated in this article, for new approaches and efforts to understand how commercialization shapes the practice of microfinance in the lives of its clients.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, Borrowers" socio-demography, previous attitude and credit record have substantial influences on recovery rate (Baklouti, 2013). Van den Berg, Lensink, and Servin (2015) found that characteristics of loan officer, more specifically their gender, play a significant role on recovery rate. Hsu (2016) qualitative data analysis revealed that social ties among the borrowers are very influential in making repayment decision.…”
Section: Loan Recovery and Defaultmentioning
confidence: 99%
“…Thus, Reference [33] analyzes how certain aspects of gender relations in Malawi facilitate and constrain the impact of microcredit and found that the new interest in client-led microfinance presents an opportunity. In addition, the authors of [34] conducted a study in Mexico showing that loan officers play a crucial role in improving repayment rates in microfinance, and that male loan officers are more able to induce borrowers to repay than female loan officers.…”
Section: Microcredit Repayment and Gendermentioning
confidence: 99%